Zależność emisji CO2 z gleby od warunków atmosferycznych w podokresach zmienności respiracji gleby - Wroński, Krzysztof (Leśne Prace Badawcze, 2026)
Soil respiration was measured on rusty soil in a dry forest near Łódź. A two-year series of soil respiration was divided into characteristic sub-periods and relationships between CO 2 emission from the soil as well as selected aspectsof climatic conditions were examined. The temperature dependence of CO 2 fluxes from the soil is linear from March to June and expotential during the period from June to March. Dividing the year into aphase of growth and a phase of decline and modeling soil respiration for each of these sub-periods separately does not significantly improve the accuracy of the model. The studies have also shown that soil respiration responds with a delay of three days to changes in temperature and relative moisture,but with a 17-day delay to changes in precipitation.